Understanding Indonesian People Borrowing Money from Banks and Non-Banking Institutions - Hindun, Roro; Reza, Izzul Fatchu (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
People’s borrowing behaviours are influenced by the need to fulfil their basic needs which always change in maintaining their lifestyles. This thesis analyzes the tendency of Indonesians to borrowing money, either from banks or non-banking institutions. This research was carried out using quantitative data analysis with secondary data from the Indonesian Family Life Survey panel data versions 3 and 4. The data was analyzed using STATA 12.0 software. The results of the study show that the significant factors that affect people’s behaviour in borrowing from either banks or non-banking institutions are amount of debt, assets, income, and location; while the insignificant factors are age, religion, and number of householders. Keywords: money borrowing, borrowing behaviour, debt, IFLS, STATA